The RNA Chaperone Protein Hfq Regulates the Characteristic Sporulation and Insecticidal Activity of Bacillus thuringiensis - Yu, Zhaoqing; Fu, Yang; Zhang, Wei; Zhu, Li; Yin, Wen; Chou, Shan-Ho; He, Jin (Frontiers in Microbiology, 2022)
Bacillus thuringiensis is one of the most widely used bio-insecticides at present. It can produce many virulence factors and insecticidal crystal proteins during growth and sporulation. Hfq, on the other hand, is a bacterial RNA chaperone that can regulate the function of different kinds of RNAs, thereby affecting various bacterial phenotypes. To further explore the physiological functions of Hfq in Bacillus thuringiensis, we took BMB171 as the starting strain, knocked out one, two, or three hfq genes in its genome in different combinations, and compared the phenotypic differences between the deletion mutant strains and the starting strain. We did observe significant changes in several phenotypes, including motility, biofilm formation, sporulation, and insecticidal activity against cotton bollworm, among others. Afterward, we found through transcriptome studies that when all hfq genes were deleted, 32.5% of the genes in Bacillus thuringiensis were differentially transcribed, with particular changes in the sporulation-related and virulence-related genes. The above data demonstrated that Hfq plays a pivotal role in Bacillus thuringiensis and can regulate its various physiological functions. Our study on the regulatory mechanism of Hfq in Bacillus thuringiensis, especially the mining of the regulatory network of its sporulation and insecticidal activity, could lay a theoretical foundation for the better utilization of Bacillus thuringiensis as an effective insecticide.